Sistem Pendukung Keputusan Pemilihan Sepeda Lowrider Terbaik Dalam Sebuah Kontes Pameran Menggunakan Metode Electre - Tabah Yulistio; Niki Ratama (Journal of Research and Publication Innovation, 2023)
Decision Support System is an interactive system that provides information, modeling and data manipulation. The system is used to assist decision making in semi-structured situations and unstructured situations, where a person knows exactly how decisions must be made. Decision Support Systems are more intended to support management in carrying out analytical work in less structured situations with unclear classifications. Selection of the best Lowrider Bike will determine the final outcome of the lowrider bicycle contest. For this reason, the organizing committee for the lowrider bike competition needs to formulate an alternative for choosing the right lowrider bike. The definition of ELECTRE (Elimination Et Choix Traduisant La Realite) is a method of compiling a ranking sequence through pairwise comparisons between alternatives and the appropriate criteria. The ELECTRE method is an effective method for MADM (Multiple Attribute Decision Making) with qualitative features, so that it can improve the ability to make decisions.